O agronegócio brasileiro: hegemonia e projeto de sociedade - Severo, Marconi (2023)
Among the current conceptions of the Brazilian rural environment, especially regarding its agricultural dimension, one in particular has stood out, the economic-productive concept of agribusiness, also called agricultural business. Agribusiness is not only an economic phenomenon, but also a cultural, political and social phenomenon that claims to be the authentic representative of rural people, although it is not limited to the rural environment: it aims at society as a whole. Its hegemony is based on a universalizing discourse centered, in turn, on the figure of the productive rural producer. This discourse has the ability to mobilize individual pre-dispositions typical of modern urban-industrial societies, mostly experienced as doxas that assure its self-promotion while allowing it to disqualify and stigmatize its critics and opponents. It is these same pre-dispositions, when strategically mobilized, that allow agribusiness to use the rural middle class, that is, those farmers situated between the most capitalized strata of family farming and entrepreneurial and patronal farming, as a sort of barrier class in defense of its interests and hegemony. This paper, therefore, is dedicated to the study of the constitution and mobilization of the hegemony of Brazilian agribusiness, which is equivalent, to some extent, to the study of the social configuration of the rural milieu itself.